Profiling FLT3 Mutations in Mexican Acute Myeloid Leukemia Pediatric Patients: Impact on Overall Survival - Molina Garay, Carolina; Carrillo Sánchez, Karol; Flores Lagunes, Luis Leonardo; Jiménez Olivares, Marco; Muñoz Rivas, Anallely; Villegas Torres, Beatríz Eugenia; Flores Aguilar, Hilario; Núñez Enríquez, Juan Carlos; Jiménez Hernández, Elva; Bekker Méndez, Vilma Carolina; Torres Nava, José Refugio; Flores Lujano, Janet; et al. (Frontiers in Pediatrics, 2020)
Background: Acute Myeloid Leukemia is the second most frequent leukemia in childhood. The FLT3 gene participates in hematopoietic stem cell proliferation. FLT3 mutations are recurrent in AML and influence prognosis. In Mexican pediatric AML patients, FLT3 mutational profile and their clinical impact have not been evaluated. Aim of the study. Identify the profile of FLT3 mutations in pediatric patients with de novo AML and assess their possible influence on overall survival (OS) and other clinical features. Methods: Massive parallel target sequencing of FLT3 was performed in 80 patients. Results: FLT3 mutations (ITD or TKD) were identified in 24% of them. OS was significantly lower in FLT3POS cases than in FLT3NEG (p = 0.03). The average OS for FLT3POS was 1.2 vs. 2.2 years in FLT3NEG. There were no significant differences in the child’s sex, age, percentage of blasts in bone marrow aspirate, or white blood cell count in peripheral blood at diagnosis between both groups. No differences were identified stratifying by the mutational load (high> 0.4) or type of mutation. The negative effect of FLT3 mutations was also observed in patients with acute promyelocytic leukemia (APL). Conclusions: FLT3 mutational profile is described in Mexican pediatric AML patients for the first time. Mutated FLT3 negatively impacts the outcome of AML patients, even considering the APL group. Clinical benefit from treatment with tyrosine kinase inhibitors in the FLT3POS pediatric patients needs to be assessed in clinical trials. FLT3 testing may contribute to better risk stratification in our pediatric AML patients.